PSYCHEDELICS IN THE TREATMENT OF POST-TRAUMATIC STRESS DISORDER AND DEPRESSION: A REVIEW OF CLINICAL TRIALS - Anna Maria Szeszko; Weronika Maria Czernek; Magdalena Cichorzewska; Martyna Płachta; Rafał Marcin Wojtan; Małgorzata Lubowiecka (International Journal of Innovative Technologies in Social Science, 2026)
Psychedelic-assisted therapy has emerged as a prominent area for psychiatric investigation particularly with regards to treatment-resistant depression and Post Traumatic Stress Disorder (PTSD). The purpose of this narrative review was to outline the current body of research regarding psychedelic and psychedelic-like compounds in these two psychiatric conditions highlighting psilocybin-assisted therapy for depression and 3,4-methylenedioxymethamphetamine-assisted therapy for PTSD. Searches for this review focused on clinical trials, follow-up studies, systematic reviews and regulatory documentation published between 2016 and June 2026 that had been peer-reviewed. Evidence from this review confirms that psilocybin when used alongside a therapeutic intervention produces prompt reduction of symptoms for depression in Major depressive disorder, treatment-resistant depression, and psychological distress associated with cancer. There was also evidence of clinically significant reduction of symptoms with trials using 3,4-methylenedioxymethamphetamine for the treatment of PTSD with two phase three trials showing robust reduction in symptom scores compared to placebo-plus-therapy. The current body of evidence, however, is not as extensive or as simple as has been suggested, and has several limitations: low sample sizes in multiple studies, difficulty in functioning blinded treatment groups, expectations in patients and therapists, inadequate length of follow up, a lack of demographic diversity in participants, high treatment requirements, a developing understanding of appropriate models of psychotherapy, and several unsolved safety and regulatory questions. Psychedelic-assisted therapy is therefore an emerging intervention that has potential but it has yet to be properly understood and its future is dependent on well-conducted studies, transparent disclosure of adverse events, careful patient selection, proper therapist training, long-term assessment, and health systems that are equipped to deliver treatment safely and equitably.